PFM.38 Clinical Outcomes from a Specialist Preterm Labour Clinic: A 5 Year Overview. (9th June 2014) - Care, A; Perry, C; Roberts, D; Sharp, A; Alfirevic, Z
Abstract : Background: Specialist Preterm Labour (PTL) clinics are a relatively novel innovation and allow translation of current research into clinical practise in an effort to reduce and prevent spontaneous preterm birth (sPTB) rates. A paucity of clinical guidance in this area is testimony to their recentness. Our aim was to evaluate our clinics performance over the past 5yrs with a view to identifying auditable standards and suggestions for improvement. Method: Data was collected from January 2008–December 2012 on all new patients, including; demographics, indication for referral, cervical length, treatment, gestation at delivery and short term neonatal outcomes. Treatments include history or ultrasound indicated cerclage, vaginal progesterone and Arabin cervical pessary. Results: Data from 504 patients was collected. Demographic data and delivery data was obtained in 100% of cases, with 97% having neonatal outcome data. 100% of cervical length data was available from 2011 onwards, with 22–80% available prior. Overall referrals increased from 70patients/yr to 129 patients/yr. The most common indication for referral was previous sPTB (60%). Previous PPROM and previous cervical surgery accounted for 18% and 17% of referrals respectively, other referrals include threatened PTL. For all attendees PTB rates have improved over the 5 yrs from 40% to 27.1%. Conclusion: Our data demonstrate a development in the quality of data collection over time. In the absence of current national standards we have identified auditable standards for documentation and patient follow up. Standardisation of specialised preterm labour clinic data sets nationally will also allow for data sharing and improve clinical practice.